2022
DOI: 10.1108/itp-01-2021-0041
|View full text |Cite
|
Sign up to set email alerts
|

Supporting participatory innovation during the COVID-19 pandemic: a comparative study of enterprise social media use

Abstract: PurposeThe need for accelerating innovation is exacerbated as organizations struggle to either adapt or perish in this unforgiving condition due to the COVID-19 disruption. To address this issue, many organizations have embraced employee-driven participatory innovation to survive and thrive albeit the uncertainties. This study aims to investigate the role of enterprise social media (ESM) in supporting and facilitating these efforts.Design/methodology/approachThis study first identified the underlying mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 149 publications
0
6
0
Order By: Relevance
“…Third, prior literature also demonstrated that ESM offers many features that facilitate the function affordances for innovation-related actions (Karahanna et al, 2018). For instance, ESM provides a set of features for content-creation and content-sharing, enabling employees' ideation action that fosters innovative actions (Abhari et al, 2022;Nivedhitha and Manzoor, 2002). We thus propose that employees innovatively use ESM to help them cope with the uncertainty in the hybrid working practices, such as boundarylessness, multitasking and interruptions at work (Xie et al, 2019).…”
Section: Esm Use Behaviors In the Post-acceptance Stagementioning
confidence: 88%
See 4 more Smart Citations
“…Third, prior literature also demonstrated that ESM offers many features that facilitate the function affordances for innovation-related actions (Karahanna et al, 2018). For instance, ESM provides a set of features for content-creation and content-sharing, enabling employees' ideation action that fosters innovative actions (Abhari et al, 2022;Nivedhitha and Manzoor, 2002). We thus propose that employees innovatively use ESM to help them cope with the uncertainty in the hybrid working practices, such as boundarylessness, multitasking and interruptions at work (Xie et al, 2019).…”
Section: Esm Use Behaviors In the Post-acceptance Stagementioning
confidence: 88%
“…, 2018). For instance, ESM provides a set of features for content-creation and content-sharing, enabling employees' ideation action that fosters innovative actions (Abhari et al. , 2022; Nivedhitha and Manzoor, 2002).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations